Racial Discrimination in Health Care Is Associated with Worse Glycemic Control among Black Men but Not Black Women with Type 2 Diabetes - Assari, Shervin; Lee, Daniel B.; Nicklett, Emily Joy; Moghani Lankarani, Maryam; Piette, John D.; Aikens, James E. (Frontiers in Public Health, 2017)
Abstract Background. A growing body of research suggests that racial discrimination shapes the health of Black men and Black women differently. Aims. This study examined Black patients with DM in order to test gender differences in: 1) levels of perceived racial discrimination in health care, and 2) how perceived discrimination relates to glycemic control. Methods. A total of 163 Black patients with type 2 DM (78 women and 85 men) provided data on demographics (age and gender), socioeconomic status, perceived racial discrimination in health care, self-rated health (SRH), and hemoglobin A1c (HbA1c). Data were analyzed using linear regression. Results. Although racial discrimination in health care was not significantly associated with either SRH or HbA1c in the pooled sample (b=.20, 95% CI= -.41 - .80), gender-stratified analyses indicated that perceived discrimination was associated with higher HbA1c levels for Black men (b=.86, 95% CI=.01 - 1.73) but not Black women (b=-.31, 95% CI=-1.17 - .54). Conclusions. Consistent with previously demonstrated gender differences in the discrimination-health link for non-diabetes patients, perceived racial discrimination in diabetes care was associated with higher HbA1c for Black men, but not for Black women. Scholars and clinicians should take gender into account when considering the impacts of race-related discrimination experiences on health care outcomes.